PROGRAM SEKOLAH LAPANG BUDIDAYA UNTUK PEMBUDIDAYA IKAN BANDENG (Chanos chanos) DI WILAYAH PESISIR KOTA PEKALONGAN - Heri Ariadi; Tri Yusufi Mardiana; Linayati Linayati; M.B. Syakirin; Benny Diah Madusari; Hayati Soeprapto; Abdul Wafi (LP2M Universitas Ibrahimy, 2023)
The purpose of this service was to actualization the of milkfish cultivation field school activities implementation in the Pekalongan City coastal. The service method used was counseling activities with a certain thematic coupled with field practice. Then, the activity participants were given a question instrument questionnaire. The results of the analysis of this community service activity showed that the majority respondents (12 people) stated that there was an increase in knowledge related to procedures for cultivating fish after joining the program. Additionally, from participating survey their insights increased and their mastery of technology also became more proficient, and they gained new relationships. In general, this program was very beneficial for them as program recipients, with the impact of increasing their mastery of activity material by 60-99%. The level of mastery of the material was 60-99%, with 6 people responding 60-79%, 5 people responding 80-99%, and 1 person responding >60%. The conclusion of the milkfish cultivation field school activities in the coastal area of Pekalongan City was that, in terms of evaluation, it was very good. Milkfish cultivation field school activities proved to be an effective means of transferring information from researcher or academician to fish farmers in the Pekalongan area.